Genetic Risk Score Improves Risk Stratification for Anticoagulation-Related Intracerebral Hemorrhage. Issue 3 (9th February 2023) - Mayerhofer, Ernst; Parodi, Livia; Prapiadou, Savvina; Malik, Rainer; Rosand, Jonathan; Georgakis, Marios K.; Anderson, Christopher D.
Abstract : Background: Intracerebral hemorrhage (ICH) is the most devastating adverse outcome for patients on anticoagulants. Clinical risk scores that quantify bleeding risk can guide decision-making in situations when indication or duration for anticoagulation is uncertain. We investigated whether integration of a genetic risk score into an existing risk factor–based CRS could improve risk stratification for anticoagulation-related ICH. Methods: We constructed 153 genetic risk scores from genome-wide association data of 1545 ICH cases and 1481 controls and validated them in 431 ICH cases and 431 matched controls from the population-based UK Biobank. The score that explained the largest variance in ICH risk was selected and tested for prediction of incident ICH in an independent cohort of 5530 anticoagulant users. A CRS for major anticoagulation-related hemorrhage, based on 8/9 components of the HAS-BLED score, was compared with a combined clinical and genetic risk score incorporating an additional point for high genetic risk for ICH. Results: Among anticoagulated individuals, 94 ICH occurred over a mean follow-up of 11.9 years. Compared with the lowest genetic risk score tertile, being in the highest tertile was associated with a two-fold increased risk for incident ICH (hazard ratio, 2.08 [95% CI, 1.22–3.56]). Although the CRS predicted incident ICH with a hazard ratio of 1.24 per 1-point increase (95% CI [1.01–1.53]), adding a point for high genetic ICH risk led to a stronger association (hazard ratio of 1.33 per 1-point increase [95% CI, 1.11–1.59]) with improved risk stratification (C index 0.57 versus 0.53) and maintained calibration (integrated calibration index 0.001 for both). The new clinical and genetic risk score showed 19% improvement in high-risk classification among individuals with ICH and a net reclassification improvement of 0.10. Conclusions: Among anticoagulant users, a prediction score incorporating genomic information is superior to a clinical risk score alone for ICH risk stratification and could serve in clinical decision-making.